I'jaz in the Qur'an through the Use of the Word Bayt to Designate the Ka'aba Before its Rebuilt by Quraysh: Lessons for the Revivification of the Awqaf Knowledge - Belabes, Abderrazak Said (QiST: Journal of Quran and Tafseer Studies, 2025)
The aim of the research is to highlight the inimitability of the Qur'an through the use of the word Bayt, over a long period, to designate what has become known as Ka'aba. Initially, the building had a rectangular shape, with a semi-circular shape on the north side, since Ibrahim had rebuilt it with the help of his son Isma'il. The cubic shape dates back to five years before the advent of Islam when Quraysh had rebuilt it after it was partly destroyed by a torrential rain. Hence the name Ka'aba which means cube in Arabic. This explains why the use of the word bayt in the Qur'an, under different forms, is more than five times greater than that of Ka'aba. This i'jaz of the Qur'an in the judicious choice of words that accord with proven historical facts is paramount in the Revivification of the Awqaf Knowledge. The word Bayt refers to the House of Allah as a Habs, that is, something that remains under the Mulk (Sovereignty) of Allah. This is the case by extension for any place of worship as al-Bukhari mentions through one of his titles in his Collection of Authentic Ahadith. In this regard, the word Bayt is deeper than that of Ka'aba, because it contains strata of meaning that are not found through the word Ka'aba, and allows, consequently, to link things that the word Ka'aba does not allow, by immersing us in the deep history of humanity in its innate state which pushes to sincerity of worship for Allah. Thus, in terms of the organization of life, in the beginning was the Rizq of Allah, which generated the building of the Bayt as a Habs, then came the Ma'ash to provide for those who visit it to worship Allah, and the 'Umran following the grouping of people to dwell around the House of Allah.